2020
DOI: 10.1080/15384047.2019.1702405
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA FTX inhibition restrains osteosarcoma proliferation and migration via modulating miR-320a/TXNRD1

Abstract: It was well established that long non-coding RNAs (LncRNAs) could serve as oncogene or tumor suppressor in terms of the tumor type. FTX, as a member of lncRNA family, has been reported to be associated with several tumor progressions, such as hepatocellular carcinoma (HCC), renal cell carcinoma (RCC) and colorectal cancer. However, the regulatory role of FTX in osteosarcoma (OS) still lacks research analysis. This paper aims to explore how FTX exerts its regulatory role on OS by modulating TXNRD1/ miR-320a, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Specifically, numerous miRNAs, participating in LUAD development, were reported to be regulated by lncRNAs [26][27][28]. FTX has been supported as a ceRNA in several tumors, such as hepatocellular carcinoma [29], osteosarcoma [30] and colorectal cancer [14]. Herein, our present study first showed that FTX was a cytoplasmic RNA and interacted with miR-335-5p in LUAD.…”
Section: Discussionmentioning
confidence: 49%
“…Specifically, numerous miRNAs, participating in LUAD development, were reported to be regulated by lncRNAs [26][27][28]. FTX has been supported as a ceRNA in several tumors, such as hepatocellular carcinoma [29], osteosarcoma [30] and colorectal cancer [14]. Herein, our present study first showed that FTX was a cytoplasmic RNA and interacted with miR-335-5p in LUAD.…”
Section: Discussionmentioning
confidence: 49%
“…LncRNA FTX was firstly identified in XIST gene locus and was dysregulated in many human cancers [ 15 , 35 , 36 ]. FTX is located upstream of XIST , within the X-inactivation center, and produces a spliced lncRNA which positively regulate the expression of XIST , which is essential for initiation and spread of X-inactivation (provided by RefSeq, May 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of promoting cancer by FTX may be involved in the following aspects.FTX signi cantly promoted proliferation and invasion of glioma cells by negatively regulating miR-342-3p [24]; FTX exerted its oncogenic role in OSC via up-regulating the expression of TXNRD1 through sponging miR-320a [25];…”
Section: Discussionmentioning
confidence: 99%